1997
DOI: 10.1007/bf02054976
|View full text |Cite
|
Sign up to set email alerts
|

A clinical trial to evaluate the worth of preoperative multimodality therapy in patients with operable carcinoma of the rectum

Abstract: These data do suggest that the preoperative chemotherapy and radiation therapy regimen used are, at least, as safe and tolerable as standard postoperative treatment. There is presently a trend to tumor downstaging and sphincter preservation in the preoperative arm. Whether this arm will have greater or lesser survival and long-term toxicity awaits the completion of this relevant study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
121
1
16

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(146 citation statements)
references
References 26 publications
8
121
1
16
Order By: Relevance
“…We found that patients with pCR had better disease-specific survival than those with either post-treatment stage I or stage IIA disease. Our data is consistent with the previous findings from other carcinoma sites that pCR is associated with better prognosis [24][25][26][27][28][29]. Given the rarity and the limited number of patients with PDA who received neoadjvant CRT had pCR in pancreatectomy reported in this study, future collaborative studies of a larger patient population is needed to confirm the prognostic values of pCR in patients with PDA.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that patients with pCR had better disease-specific survival than those with either post-treatment stage I or stage IIA disease. Our data is consistent with the previous findings from other carcinoma sites that pCR is associated with better prognosis [24][25][26][27][28][29]. Given the rarity and the limited number of patients with PDA who received neoadjvant CRT had pCR in pancreatectomy reported in this study, future collaborative studies of a larger patient population is needed to confirm the prognostic values of pCR in patients with PDA.…”
Section: Discussionsupporting
confidence: 92%
“…The extent of residual invasive adenocarcinoma in post-therapy specimens has been shown to correlate with the prognosis in patients with several types of carcinomas, including PDA, esophageal cancer, and rectal cancer [24][25][26][27][28][29]. In our previous study of 240 patients with PDA who received neoadjuvant CRT and pancreaticoduodenectomy, we showed that posttherapy tumor stage (ypT), lymph node status (ypN), and the post therapy AJCC pathologic stage were independent prognostic factors of both disease-free and overall survivals in this group of patients [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several phase II studies of 5-fluorouracil-based preoperative chemoradiotherapy for locally advanced rectal cancer have reported R0 resection rates of 60 -85% (Chan et al, 1993;Minsky et al, 1993;Keilholz et al, 1995;Videtic et al, 1998;Küchenmeister et al, 2000;Rödel et al, 2000) including pathologic complete response (pCR) rates of 5 -20%. Even in low rectal tumours, sphincter-preserving surgery was possible after preoperative chemoradiotherapy in 27 -86% of the patients (Grann et al, 1997;Hyams et al, 1997;Maghfoor et al, 1997;Küchenmeister et al, 2000). Moreover, randomised trials have shown that neoadjuvant chemoradiotherapy improves local control compared with postoperative chemoradiation in primary resectable tumours (Roh et al, 2001;Sauer et al, 2004).…”
mentioning
confidence: 99%
“…Results expressed as percentages of patients who were evaluable at each dosage level are shown above each bar (Minsky et al, 1992a) need to monitor the results of treatment and respond appropriately. The need for more effective liaison between different clinical disciplines is illustrated by the observation that preoperative radiation therapy or combined modality therapy in patients with rectal cancer who undergo surgery may be associated with a more favourable outcome (reduced toxicity and better preservation of sphincter function) than post-operative therapy (Minsky et al, 1992ci;Rouanet et al, 1995;Hyams et al] 1997;Maghfoor et al, 1997). An example of how patient-centred end-points such as reduced incidence of acute side-effects and the avoidance of permanent colostomy might be used to improve the overall effectiveness of treatment is shown by the following data from the Memorial Sloan-Kettering Cancer Center (Minsky et al, 1992a).…”
Section: Designing Therapies To Enhance Patient-centred Outcomesmentioning
confidence: 99%